Influences of oral cryotherapy on mucositis prevention in cancer patients with chemotherapy - Nataria Yanti Silaban; Siti Saidah Nasution; Cholina Trisa Siregar (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: A mucositis is the most common problem in a chemotherapy treatment and becomes a severe problem for patients who receive several cycles of chemotherapy. Effects of an oral mucositis that is not treated immediately or is less effective can affect quality of life of the patients. Pain experienced by them can cause problems in the mouth, for example inability to tolerate food or fluids (dysphagia) and decreases of nutritional status.Objective: This study is to identify effectiveness of oral cryotherapy on prevention of the mucositis in cancer patients with chemotherapy.Methods: This study used a quasi-experimental method with a pre and post-test for a control group. Its samples were 32 patients for an intervention group and a control group, taken by using a consecutive sampling technique. The mucositis was measured by using questionnaires of Oral Assessment Guide (OAG), and the obtained data was analysed by the Wilcoxon and Mann Whitney test.Results: This study found that 24 respondents were not affected by the mucositis at p-value=0.008 (p<0.05) in the post intervention in the intervention group, and there was a difference in values of the mucositis measured by the OAG at p-value=0.003 (p<0.05) in the post intervention in the both groups.Conclusion: The oral cryotherapy could prevent the mucositis in cancer patients with chemotherapy.